PERSEPSI SISWA KELAS XI TERHADAP KEGIATAN MANAJEMEN KELAS OLEH GURU DI SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) 2 PADANG - Cici Trisia (Jurnal Bahana Manajemen Pendidikan, 2018)
The purpose of this research is to observe information about student perception for XI class toward the class management activities by teacher at the state vocational school No. 2 Padang. This is description research. The population of research is 418 students and research sample is 81 students that was taken propotional random sampling. The research instrument is questioner by scale model of Likert that has been examined validate and reability. The analysis data by using average formula (mean). The result of this research indicated that student perception for XI class toward the class management activities by teacher at the state vocational school No. 2 Padang is in good category by using average scores 3,69 become  73,70 percant.Key words :  perception, class management.